In the kitchen a novel - Ali, Monica 1967- (Scribner, 2009)
In this story of the rich and fascinating London subculture of chefs and kitchen denizens, Gabriel Lightfoot, executive chef at the once-splendid Imperial Hotel, is trying to run a tight kitchen but his integrity--to say nothing of his sanity--is under constant challenge from the competing demands of an exuberant multinational staff, a gimlet-eyed hotel management, business partners with whom he is secretly planning a move to a restaurant of his own, and a worker found dead in the kitchen's basement.
Keywords: Cooks -- Fiction; Hotels -- England -- London -- Fiction; Restaurants -- Fiction; London (England) -- Fiction; Fiktionale Darstellung